Student's life skills and stages of change in schools of Kailali district, Nepal. - Adhikari,Chiranjivi (2011)
SUMMARY: The primary objective of the study was to explore the 12 generic life skills in different stages of transtheoretical model (TTM) in key four constructs. The secondary objective of the study was to assess the wellbeing with 12 generic life skills. The study was carried out in the schools of Kailali district with two-stage random sampling. Self-administrable questionnaire was developed to assess the stages, decisional balance of pros and cons, self-confidence, study process strategy and WHO wellbeing. Total students were 596, of which 595 returned the questionnaire, indicating negligible non-response rate (0.2%). Mean age of the students was 14.9±1.6 years. Descriptive analysis was done for 595 students, however, for the sake of criterion-related validity, only 583 respondents were entered in the pool of data for inferential statistical analysis, that is, age below 12 years and above 18 years was excluded. The questionnaire was developed only after consulting the experts from the field of education, psychology and supervisors. The collected data was entered and analysed in SPSS version 17.0. The descriptive statistics showed the unequal distribution of proportion of students across stages of change of various life skills, which is consistent with the previous studies. The change of pros is progressing and the change of cons decreasing across the stages from precontemplation through maintenance as in predicted direction, showing some exceptions. Cronbach's alpha of the six items of life skills was 0.645 in this study. The scree plot of factors of decisional balance in principal component analysis showed four factors in the initial analysis but it was also significant when two factors to extract was applied. Total variance explained by the two factors was found to be 28 percent. The strong principle of TTM was not found to support the life skills whereas weak principle was found to be consistent in one pair of life skills, that is social awareness and empathy skills. Most of the correlation analysis showed significant relationship as predicted by the TTM. Wellbeing was also found, as far as the researcher had reviewed, for the first time, significant correlation with different constructs of TTM when life skills were applied. ANOVA and Tukey tests were significant in almost constructs of TTM when life skills were applied. Only one pattern was found in reverse direction, rather than predicted. Levene test was applied for the calculation of the test of the equality of variances. Cohen's d was calculated for the effect size measure and found large size effect in all life skills. The size was ranged from 1.92 to 2.46. However, the difference in precontemplation was in reverse direction, which signifies the further application of stronger design in life skills to measure its stages. Multivariate analysis was done in three models. First model was applied for the socio-demographic characteristics, second model was applied for the constructs of TTM applied with life skills and final model was done for the both of above. The final model (model 3) revealed that self confidence was associated with OR of 0.466 (95% CI, 0.254-0.856) with overt critical thinking and creative thinking skills. Likewise, occupation was associated with social awareness and empathy skills with the OR of 1.960 (95% CI, 1.336- 2.781); self confidence with self-esteem and self-responsibility with the OR of 0.405 (95% CI, 0.216-0.759); grade eight with reference to grade ten with decision making and problem solving with the OR of 1.690 (95% CI, 1.145-2.495). Overt interpersonal relationship and communication as well as coping with emotion and stress were found to be associated with two and three covariates respectively. The former was significant with self-confidence (OR=0.440, 95% CI, 0.237-0.817); grade nine with reference to ten (OR=1.570, 95% CI, 1.038-2.373) and cast, upper cast with reference to all other casts (OR= 1.605, 95% CI, 1.114-2.312). The later was associated with parental educational status, with reference to upper (OR=2.118, 95% CI, 1.164-3.855) and with pros, with reference to low pros (OR= 0.683, 95% CI, 0.478-0.974). Final outcome variable, wellbeing, was measured in better and low mood and covariates were all the life skills. Only self awareness and empathy overt skills found to be significantly associated with better well-being with the OR of 2.880 (95% CI, 1.668 4.973) in reference to covert skills. The study broadly supported the generic life skills as predicted by the transtheoretical model and well-being. General proportion of the students, pattern of various constructs across stages were found as predicted by the transtheoretical model. However, the strong and weak principle was not as predicted by the TTM. Mean and standard deviations were not in linear progression across the stages of change; which demands further research in life skills of stages of change with the better design. Very interestingly, in this study, students in grade eight had higher odds ratio with reference to grade ten in decision making and problem solving overt skills.